2007
DOI: 10.1086/520704
|View full text |Cite
|
Sign up to set email alerts
|

Detection of C 8 H - and Comparison with C 8 H toward IRC +10 216

Abstract: We report the detection of new transitions of octatetraynyl (C 8 H) toward the circumstellar envelope IRC ϩ10 216 using data taken with the 100 m Green Bank Telescope (GBT). In addition, we report five features from the Ku, K, and Q bands that have been identified as transitions of the octatetraynyl anion (C 8 H Ϫ ). From a rotational temperature diagram and an assumed source size of 30Љ, we find a total C 8 H column density of cm Ϫ2 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(122 citation statements)
references
References 15 publications
6
116
0
Order By: Relevance
“…Since then, it and other anions have been detected in a variety of sources (Brünken et al 2007;Remijan et al 2007;Sakai et al 2010b;Cordiner et al 2011). Rate12 includes 22 new anions, which are involved in 1280 reactions.…”
Section: Anion Reactionsmentioning
confidence: 99%
“…Since then, it and other anions have been detected in a variety of sources (Brünken et al 2007;Remijan et al 2007;Sakai et al 2010b;Cordiner et al 2011). Rate12 includes 22 new anions, which are involved in 1280 reactions.…”
Section: Anion Reactionsmentioning
confidence: 99%
“…This was later confirmed based on chemical models (Miller et al, 2007), which was then followed by detection of C 8H -and C4H -in the molecular cloud TMC-1 (BrOnken et al, 2007). C 8H -was detected within the circumstellar envelope IRC+10 216 by Remijan et al (2007). Sakai et al (2007) detected C6H-within a low-mass star-forming region of L1527 and then later Sakai et al (2008) reported the detection of C 4H-near the low-mass Class 0 protostar IRAS 04368+2557.…”
Section: Introductionmentioning
confidence: 98%
“…The molecular anions detected so far in the interstellar and circumstellar gas are all fairly heavy linear carbon chains consisting of three or more carbon atoms, and with neutral counterparts with large electron affinities: C 4 H − , C 6 H − , C 8 H − , C 3 N − , and C 5 N − (McCarthy et al 2006;Cernicharo et al 2007;Brünken et al 2007a;Remijan et al 2007;Thaddeus et al 2008;Cernicharo et al 2008). The abundance of these anions relative to the neutral counterparts increases with both size and the electron affinity of the neutral molecule, as expected for formation by radiative electron attachment (Herbst & Osamura 2008).…”
Section: Introductionmentioning
confidence: 99%